(untitled) (Al-Academy, 2026)
Spite discourse is a strategy between at least two parties, in which a specific discourse is presented, such as a product, commodity or service, to a specific recipient, as better than the competitor, or by employing the competitor’s products, services or slogans and harnessing them as a means to support the advertised material, directly or indirectly. This research aims to identify spite in contemporary graphic discourse. Which is determined spatially, temporally and thematically by studying spite in contemporary graphic discourse, specifically in the United States of America for the years (2001-2022), i.e. since the World Trade Center incident, and its repercussions on commercial advertising and up to the present time. The research was directed towards the following global agencies: (Burger King) and (MacDonald) as a model, which are the two most famous commercial agencies that have sold in the research field. The theoretical framework dealt with in its first section: Spite in contemporary graphic discourse: its nature, history, causes, and its relationship to reception and recipient, while in its second section, Spite in contemporary commercial advertising design: its types, methods, and forms. The researcher did not find a real and direct studies in his research field, but he turned to the closest research, which was: (Comparative Advertising Research: A Review and Research Agenda), published on: https://www.researchgate.net/publication/315476722 on: 2012, By a group of researchers, and I agree with most of its results, which are part of each and every method of other methods reached by the researcher. The research came out with the most important results: Spite was used as a means of indirect commercial advertising, and enabling the recipient to read the hidden discourse used against the competitor without referring to him, through suggestions that the recipient understands and teases his mind and imagination according to the aesthetics and enjoyment of reception. As in Model No. 2. The conclusions were: Advertising by spite may be a strategy that is openly against the law or evasive of it, according to the marketing plan that each commercial agency sets for its advertisements, which may sometimes mobilize the loyalty of the recipient as a party to it, through various means and media.